(untitled) (Journal of history, 2019)
Оfficial discourse (soviet and Chinese) interpreted the reasons of ethnic groups exodus etatist – border defense, L control over population migrations, economic losses and maintenance of bilateral relations at certain level. Q.Zhumadilov drew the line of affirmation of Kazakhs migration from China as salvation, but essential ethno-demographic resource for maintenance of ethnic potential of Kazakhs in soviet Kazakhstan. The official soviet discourse being diplomatic in form, especially, when it concerned the regulating technicalities with the Chinese officials, was civic in nature. The Soviet Union interpreted the right to patronize the former Russian/ soviet citizens residing in China through the mission or responsibility to protect. Although the main motivation was to gain as many loyal to the soviet regime human force for realization of state building projects within the USSR. The Chinese discourse was mainly political administrative in form, and legal in nature, as it referred to the right to supervise the population of the province and prevent intervention of alien forces into it domestic sphere